Too Pretty for Homework: Sexualized Gender Stereotypes Predict Academic Attitudes for Gender-Typical Early Adolescent Girls. (April 2019) - Nelson, Andrew A.; Brown, Christia Spears
Sexualized gender stereotypes (SGS) are commonly endorsed by adolescent girls. These stereotypes include the notion that girls can enhance their social status by prioritizing their sexualized attractiveness, which necessitates downplaying other traits such as intelligence. According to the stereotype emulation hypothesis, a girl will be more likely to "emulate" SGS if she also identifies as a typical girl. Based on this hypothesis, the current study examined the relationship between girls' SGS endorsement and their academic motivations, beliefs, and motivations—and whether this relationship was moderated by gender typicality. Girls ( N = 99), aged 11 years to 14 years ( Meanage = 12.4 years, SD = .57 years), completed a survey assessing their academic outcomes, SGS endorsement, and gender typicality. As hypothesized, results indicated that higher endorsement of SGS was generally associated with maladaptive academic outcomes, and this association was the strongest for highly gender-typical girls. Theoretical and educational implications are discussed.